Flight of three major insect pests of stored grain in the monsoonal tropics of India, by latitude, season and habitat. (March 2018) - Rajan, T. Sonai; Muralitharan, V.; Daglish, G.J.; Mohankumar, S.; Rafter, M.A.; Chandrasekaran, S.; Mohan, S.; Vimal, D.; Srivastava, Chitra; Loganathan, M.; Walter, G.H.
Abstract: The timing, extent and landscape coverage of the flight of stored product insect pests could influence their ecology differentially across climatic zones. We therefore assessed the seasonal flight patterns of Tribolium castaneum (Herbst), Rhyzopertha dominica (F.) and Sitophilus oryzae (L.) monthly, for 18 months, in three habitats (around bulk grain storage, in cropping habitats, and in mixed orchard habitats) in southern India (Coimbatore and Thanjavur) and northern India (New Delhi) using pheromone traps. We tested for species-specificity in their seasonal flight patterns as well as regional variation. Vastly more beetles were trapped near bulk grain storages than in cropping and orchard habitats. In both southern and northern India, T. castaneum was most numerous, with numbers much higher in southern India. Rhyzopertha dominica was more commonly trapped in New Delhi, a wheat producing region, than in the rice producing south. The numbers of T. castaneum trapped across time and geographical location varied significantly, with peak flight activity during the post-monsoon period (October). By contrast, R. dominica in New Delhi peaked once during summer (May) around bulk storage but tended to be more consistent (but far less numerous) in habitats away from storage. Only a few S. oryzae were caught in pheromone traps. The mean trap catches of T. castaneum in Thanjavur and New Delhi showed significant positive correlations with minimum temperatures, whereas those of R. dominica in New Delhi were significantly correlated with maximum temperatures. The patterns recorded are consistent with results recorded on other continents, but temperature thresholds for flight need to be examined in this context. A major difference was that beetles, especially T. castaneum, were captured far less frequently in traps away from storage in India than in Australia, a pattern that needs to be confirmed before a biological basis for it is sought. Highlights: Seasonal flight patterns of key stored grain beetle pests were quantified in different regions and habitats in the monsoonal tropics of India. Significantly more beetles were trapped near bulk grain storages than in cropping and mixed orchard areas. The most prevalent species was Tribolium castaneum (more numerous in south India), followed by Rhyzopertha dominica (more prevalent in north India). Flight of key stored grain insect pests was strongly seasonal in north India but not in the south.